All Days 2013
DOI: 10.2118/168086-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Field Application of a New Chemical Treatment in a Fluid Blocked Well in Saudi Arabia

Abstract: A successful trial of the Gas Well Stimulant WS-1200 was recently completed on a gas well with high Condensate-Gas Ratio (CGR) and producing below the dew point to treat fluid blockage in Saudi Arabia. The treatment consisted of pumping from a surface 2 wt% active solution in common organic solvents that solubilizes and/or displaces the brine and condensate that are present in the near wellbore region of a fluid blocked well. After bullheading the treatment into the well, it was chased with two equivalents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Был проведен ряд иссле дований, направленных на рассмотрение этого случая, которые показали, что переход от однофазного к многофазному течению около скважины приводит к образованию скопления конденсата. Согласно [38] когда конденсат образу ется вблизи ствола скважины, он создает три различные области подвижнос ти в резервуаре. В области, где давление жидкости еще выше давления точки росы, есть только одна газовая фаза.…”
Section: м а териа л ы и м етодыunclassified
“…Был проведен ряд иссле дований, направленных на рассмотрение этого случая, которые показали, что переход от однофазного к многофазному течению около скважины приводит к образованию скопления конденсата. Согласно [38] когда конденсат образу ется вблизи ствола скважины, он создает три различные области подвижнос ти в резервуаре. В области, где давление жидкости еще выше давления точки росы, есть только одна газовая фаза.…”
Section: м а териа л ы и м етодыunclassified
“…When the drawdown pressure hit below the dew point pressure, a small drop of condensate is formed and accumulated in the near wellbore region. As the accumulation occurs, the liquid saturation will also increase and the gas relative permeability is reduced, hence affecting the productivity (5,6).…”
Section: E T H O D O L O G Ymentioning
confidence: 99%
“…They concluded that methanol/water mixtures were ineffective in removing condensate bank, while methanol and the mixture of isopropanol and methanol were effective in removing water from core samples. Alzate et al (2006) performed compatibility tests between reservoir fluids, alcohol, and inhibited diesel-based treatments, and they used formation cores from Cupiagua field. They found that compatibility is a function of the miscibility of alcohol in formation fluids, volumetric concentration of alcohol in the mixture, and the composition of the fluids.…”
Section: Use Of Solventsmentioning
confidence: 99%